Association between rewarming duration and neurological outcome in out-of-hospital cardiac arrest patients receiving therapeutic hypothermia. (1st January 2020) - Hifumi, Toru; Inoue, Akihiko; Kokubu, Nobuaki; Hase, Mamoru; Yonemoto, Naohiro; Kuroda, Yasuhiro; Kawakita, Kenya; Sawano, Hirotaka; Tahara, Yoshio; Nishioka, Kenji; Shirai, Shinichi; Hazui, Hiroshi; et al.
Abstract: Aim: The European Resuscitation Council guidelines recommend a slow rate of rewarming of 0.25 °C/h–0.5 °C/h for out-of-hospital cardiac arrest (OHCA) patients receiving therapeutic hypothermia (TH). Conversely, a very slow rewarming of 1 °C/day is generally applied in Japan. The rewarming duration ranged from less than 24 h up to more than 50 h. No randomized control trials have examined the optimal rewarming speed for TH in OHCA patients. Therefore, we examined the association between the rewarming duration and neurological outcomes in OHCA patients who received TH. Methods: This study was a secondary analysis of the Japanese Population-based Utstein-style study with defibrillation and basic/advanced Life Support Education and implementation-Hypothermia (J-PULSE-HYPO) study registry, a multicenter prospective cohort study. Patients suffering from OHCA who received TH (target temperature, 34 °C) after the return of spontaneous circulation from 2005 to 2011 in 14 hospitals throughout Japan were enrolled. The rewarming duration was defined as the time from the beginning of rewarming at a target temperature of 34 °C until reaching 36 °C. The primary outcome was an unfavorable neurological outcome at hospital discharge, i.e., a cerebral performance category of 3–5. Results: The J-PULSE-HYPO study enrolled 452 OHCA patients. Of these, 328 were analyzed; 79.9% survived to hospital discharge, of which 56.4% had a favorable neurological outcome. Multivariable logistic regression analysis revealed that the rewarming duration was independently associated with unfavorable neurological outcomes [odds ratio (per 5 h), 0.89; 95% confidence interval, 0.79–0.99; p = 0.032]. Conclusion: A longer rewarming duration was significantly associated with and was an independent predictor of favorable neurological outcomes in OHCA patients who received TH.